2023
DOI: 10.1177/13505076231201445
|View full text |Cite
|
Sign up to set email alerts
|

Generative artificial intelligence and academia: Implication for research, teaching and service

Amon Barros,
Ajnesh Prasad,
Martyna Śliwa

Abstract: In this editorial, we identify some of the opportunities and the consequences of generative artificial intelligence for academia. We discuss how generative artificial intelligence will affect the three main areas of an academic’s job responsibilities: research, teaching and service. To animate our ideas, we offer illustrative examples of how generative artificial intelligence will impact each of these areas. Further recognizing that generative artificial intelligence poses both opportunities and consequences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This can significantly increase research engagement and output. Research suggested similar findings of playing significant role of institutions 11 . TMSS Medical College authority took several initiatives to motivate its staff to conduct and publish research.…”
Section: Motivation Towards Research and Publicationsupporting
confidence: 58%
“…This can significantly increase research engagement and output. Research suggested similar findings of playing significant role of institutions 11 . TMSS Medical College authority took several initiatives to motivate its staff to conduct and publish research.…”
Section: Motivation Towards Research and Publicationsupporting
confidence: 58%
“…Educators need to conform to destiny improvements to ensure the next era benefits (Qadir, 2023). Barros et al (2023) tested the effect of generative synthetic intelligence on academia, highlighting both effective and negative results from a managementlearning angle. Watermeyer et al (2023) discussed the neoliberal transformation inside the United Kingdom, which has caused academic overwork and precarity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Changing Environment for Research. Researchers from a variety of fields, including education, computer science, philosophy, communication, sociology, neuroscience, management and psychology, are involved in the interdisciplinary field of artificial intelligence in education and teaching [7][8][9]. This is particularly true with regard to research on ChatGPT, since it has been growing quickly and the course and evolution of its future are still very much up in the air.…”
Section: Introductionmentioning
confidence: 99%